Detection of β-agonists in pork tissue with novel electrospun nanofibers-based solid-phase extraction followed ultra-high performance liquid chromatography/tandem mass spectrometry. (15th July 2017) - Chu, Lanling; Zheng, Shenglan; Qu, Bin; Geng, Shiwei; Kang, Xuejun
Highlights: A novel method of nanofiber extraction has been developed for β-agonists. Selective composite nanofibers were fabricated and characterized. The nanofibers were utilized to prepare the homemade extraction cartridge. The simple extraction column displayed preferable extraction performance. The method is sensitive and cost-effective in polar analytes of complex matrix. Abstract: A selective analytical method based on packed-fiber solid-phase extraction and ultra-high performance liquid chromatography–tandem mass spectrometry (PFSPE-UPLC–MS/MS) has been developed for determination of six β-agonists (clorprenaline, bambuterol, clenbuterol, brombuterol, mabuterol, and penbuterol) in pork tissue. Polystyrene-polymeric crown ether (PS-PCE) composite nanofibers were fabricated by electrospinning and utilized to prepare the homemade extraction columns. With optimal conditions, all analytes were separated very well and the blank pork did not disturb the determination, and the linearity is good in a range of 5.0 μg/kg–25.0 μg/kg. The recoveries were 79.3–110.1%. RSDs for intra-day were in the range of 1.5–10.5% and RSDs for inter-day were 4.7–11.8%. Above all, only 5 mg of sorbent and 200 μL of elution solvent were favorable to directly extract all analytes in a complex matrix. The method is simple and cost-effective, and has the potential to be applied to quantitatively analyze the concentrations of polar species in food samples containing complex matrix.